A synthetic interaction screen identifies factors selectively required for proliferation and TERT transcription in p53-deficient human cancer cells. - Li Xie; Claude Gazin; Sung Mi Park; Lihua J Zhu; Marie-anne Debily; Ellen L W Kittler; Maria L Zapp; David Lapointe; Stephane Gobeil; Ching-Man Virbasius; Michael R Green (PLoS Genetics)
Numerous genetic and epigenetic alterations render cancer cells selectively dependent on specific genes and regulatory pathways, and represent potential vulnerabilities that can be therapeutically exploited. Here we describe an RNA interference (RNAi)-based synthetic interaction screen to identify genes preferentially required for proliferation of p53-deficient (p53-) human cancer cells. We find that compared to p53-competent (p53+) human cancer cell lines, diverse p53- human cancer cell lines are preferentially sensitive to loss of the transcription factor ETV1 and the DNA damage kinase ATR. In p53- cells, RNAi-mediated knockdown of ETV1 or ATR results in decreased expression of the telomerase catalytic subunit TERT leading to growth arrest, which can be reversed by ectopic TERT expression. Chromatin immunoprecipitation analysis reveals that ETV1 binds to a region downstream of the TERT transcriptional start-site in p53- but not p53+ cells. We find that the role of ATR is to phosphorylate and thereby stabilize ETV1. Our collective results identify a regulatory pathway involving ETV1, ATR, and TERT that is preferentially important for proliferation of diverse p53- cancer cells.